Discovery of the presence of God: devotional nonduality - Hawkins, David R. (Hay House, 2021)
"Reissue: The sixth book in Dr. Hawkins's progressive series is primarily an instruction manual for the serious spiritual devotee, revealing information that is known only by those who have transcended the ego to reach Divine Realization. This is the inner route from the self to the Self, and the descriptions of the progressive states are devoted to the reader's own illumination. While the subjective states of the mystic have been of great interest, historically, they never have been clarified to the degree presented in this semiautobiographical account that also provides the means by which to identify their rare occurrence and thus describe the core characteristics of Spiritual Truth. Free from strict religious doctrine or belief systems, the pristine essence of all Spiritual Truth is revealed in its purity with unprecedented clarity. It becomes clear that to truly know is to be, rather than to know about. This is the essence of what Hawkins calls "devotional nonduality.""--